Geografia dos sentidos: a atuação do professor de geografia no processo de inclusão - Silveira, Valdemir Cardoso da (2009)
The intention of this research agrees to explain the practise of the researcher teacher front the challenges about the inclusion of the youngs and adults, specially students who have vision default or classmates within special needs, in a school with distinguished time and space. The research, that uses as methodology and trial of the case, means the procedure of the experts, as destached an enviroment of the teaching for yougs and adults core as Pierre Bonhomme , foud out in a Campinas town, as researched people, a team of 40 classmates, between them 10 visual defaults during trials of 2005, 2006 and 2007. After the discussion about the concepts as researcher professor reflexive, curricular, included/desicluded educational inovation and geography teaching, the research underlines/appoints a historical setup to legislate the inclusion and education of the youngs and adults. Therever, the research appoints many screens: Campinas town, CEMEFEJA Pierre Bonhomme and the microcosmus the scientifical place of the Geography studies qhere event sutudied included practises. In the research, the responsour looks over the building of the history of the social changes of the classmates/students and practises which come to na included seems Geography where based to default where is based to defaul vision classmates/students and the consequences or outcomes from these practises of it transformation as research teacher reflexive